PENYESUAIAN POLA DASAR SISTEM FERNANDO BURGO PADA WANITA DEWASA BERTUBUH IDEAL DI INDONSIA - Fitria, Lusi; Ernawati, Ernawati; Nemira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The basic pattern of Fernando burgo’s system which is written in the third book of Modelismo is from Italy. It is not yet known if the use of this pattern is suitable for Indonesian women with an ideal body. The aims of this research is to describe the flaws, to illustrate how to improve the flaws and to adjust the basic foundation within the use of Fernando burgo’s system to the Indonesia slim women. This research is an applied research. The research objects are 23 years old iwomen with 163 cm height and 52 kg weight. The research instrument used is assessment form. The assessment was conducted by 5 panelists who are fashion lecturers. The analysis techniques used is descriptive statistic. The result of the research shows that the basic pattern of Fernando Burgo’s system has some flaws to used for Indonesian women with ideal typed of body. The flaws are 1). The centre front neckline is higher for 1 cm. 2) the lowest shoulder line shifts backward for 1 cm. 3). The front body block is wider for 1 cm. 4) the hipline is narrower for 2cm. The ways to improve those flaws are 1) the centre front neckline has to be lower for 1 cm. 2) the lowest back shoulder line has to be higher for 1cm and the lowest front shoulder line has to be lower for 1 cm. 3) the front body width has to be reduced by 0.5 cm for the half front block 4) the hip dimension has to be added 0.5 cm for the quarter skirt block. The adjustment were obtained by adjusting the result of the previous pattern and manipulate the formula which is used in Fernando burgo’s formulation for Indonesian women with ideal typed of body.Keyword : Adjustment, Fernando Burgo’sbasic pattern system, Indonesia ideal women